Aplicación de la contabilidad de costos en la fábrica de accesorios plásticos para riego Kaliflex del sitio San Vicente de la ciudad de Piñas, durante el mes de septiembre 2014 - Armijos Armijos, Zoila Yanina (2015)
This research paper entitled "Implementation of the cost accounting ACCESSORIES PLASTICS FACTORY SITE FOR IRRIGATION KALIFLEX SAN VICENTE PIÑAS CITY DURING SEPTEMBER 2014." It was developed as a requirement for obtaining title Engineering Accounting and Auditing Auditor Accountant (CPA), according to the regulations of the University; allowed to start counting and control the cycle of raw materials, based on purchases, labor and manufacturing costs, generating information for decision-making owner, for entrepreneurship and development of it's. They were established as targets determine the costs of manufacture and application of the accounting process for production orders, the same as were met during the execution of the investigative work; to comply with them, began with the collection of information, review of existing documentation, processes in the production and processing of accessories, the inventory of the production process was also developed, and the finished product, using the chart of accounts in accordance with the needs of the factory, in addition to the accounting records of operations according to the production of plastic accessories. After completed accounting process in KALIFLEX factory, it is concluded that it maintains a margin of approximately 30%, making sustainable this activity, highlighting that the higher the amount of production as much gain, to more effectively suggested the owner of the Accounting System implementation based on this work